(untitled) (The Agriculturists, 2014)
Banana (Musa paradisiaca) is one of the most important gigantic and oldest cultivated fruit crops grown almost everywhere in Bangladesh. Presently, the banana pseudostem is hazardous waste in Bangladesh whilst it has been used in several countries to develop important bio-products such as fibre to make yarn, fabric, apparel as well as fertilizer, fish feed, bio-chemicals, paper, handicrafts, pickles, candy, etc. Looking at this perspective, entrepreneurs of Bangladesh should take this golden opportunity and do the needful for such kind of business. The land of our country is suitable for banana production. Its fruit is a healthy diet and demandable in local markets as well as the free waste could be utilized to produce such bio-products which will contribute directly in our national economy. Thus, farmers or entrepreneurs should cultivate more banana trees in unproductive lands of coastal and hilly areas for extra income from the useless wastes and ensure eco-friendly environment. Women can also be employed in production of different bio-products from banana wastes and thus, they can contribute to their livelihood improvement. In conclusion, this review on banana waste utilization will be of help to the farmers, entrepreneurs, planners, scientists as well as Bangladesh government to take proper initiatives in socioeconomic improvement of Bangladesh. DOI: http://dx.doi.org/10.3329/agric.v12i1.19870 The Agriculturists 2014; 12(1) 148-158